sIKAP DAN KESIAPAN MAHASISWA PARIWISATA DI INDONESIA ONLINE KEGIATAN BELAJAR - Purwanti Dyah Pramanik; Santi Maudiarti; Michael Khrisna Aditya (Akademika, 2021)
Online learning is carried out in all higher education after the COVID-19 pandemic. The online learning causes forced online learning preparation. The research aimed to measure student attitudes about online learning, student readiness to learn online, and the influence of student attitudes about online learning on student readiness to learn online. The research method was descriptive quantitative and the sample was chosen by simple random sampling. The data were obtained from 311 students of the hospitality management diploma 4 of academic year 2017 to 2020 at one of the tourism school in Indonesia who had to carry out online learning. The collected data were tested using validity and reliability test, descriptive test (frequency and mean), correlation, simple linear regression test and t-test. The result of the mean test showed that students do not like online learning even though they have a perception of readiness to learn online. This result contradicted the results of the simple linear regression test and t-test which concluded that students 'attitudes of online learning positively and significantly affected students' readiness to learn online. The study implication that it is necessary to create efforts to change the attitude of being less accepting of online learning activities into an attitude of accepting online learning for students.